2020
DOI: 10.1111/his.14179
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal carcinoma has a minimal impact on Grade Group assignment in prostate cancer biopsy and radical prostatectomy specimens

Abstract: Intraductal carcinoma has a minimal impact on Grade Group assignment in prostate cancer biopsy and radical prostatectomy specimens Aims: Intraductal carcinoma (IDC) is an adverse histopathological parameter for prostate cancer outcome, but is not incorporated in current tumour grading. To account for its dismal prognosis and to omit basal cell immunohistochemistry, it has been proposed to grade IDC on the basis of its underlying architectural pattern. The aim of this study was to determine the impact of IDC gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…27 Inclusion or exclusion of IDC in tumour grading results in a global Grade Group shift in < 2% of prostate cancer biopsies. 28,29…”
Section: Clinicopathological Impact Of Individual Growth Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Inclusion or exclusion of IDC in tumour grading results in a global Grade Group shift in < 2% of prostate cancer biopsies. 28,29…”
Section: Clinicopathological Impact Of Individual Growth Patternsmentioning
confidence: 99%
“…Both the ISUP and the GUPS recommend including a comment on the association of IDC with aggressive disease, whereas the vast majority of genitourinary pathologists consider the above‐mentioned case not to be eligible for active surveillance 27 . Inclusion or exclusion of IDC in tumour grading results in a global Grade Group shift in < 2% of prostate cancer biopsies 28,29 …”
Section: Clinicopathological Impact Of Individual Growth Patternsmentioning
confidence: 99%
“…Assessment of IDC was performed on H&E slides using the criteria established by Guo and Epstein [16] minus the size criterion [14]. Presence of basal cells, corpora amylacea and branched architecture were used as criteria to differentiate IDC from invasive cribriform pattern [35]. Immunohistochemistry for basal cell markers was not performed, unless it had been requested by the diagnosing pathologist when signing out the cases, to mimic routine practice [36].…”
Section: Histopathologic Analysismentioning
confidence: 99%
“…To the Editor.-Lately, there has been debate as to whether intraductal carcinoma of the prostate (IDC) should be graded or not when it is present with concurrent invasive carcinoma, resulting in conflicting recommendations put forth by the International Society of Urological Pathology and the Genitourinary Pathology Society. 1,2 Two recent studies 3,4 have shown that grading IDC in prostate biopsies might result in Grade Group (GG) changes in~2% to 23% of cases. However, the impact of grading IDC on risk stratification of patients with prostate cancer (PCa) is somewhat unclear.…”
Section: Grading Intraductal Carcinoma In Prostate Biopsies Changes Risk Categorization In a Small Subset Of Casesmentioning
confidence: 99%